Tackling Aging by Using miRNA as a Target and a Tool. Issue 8 (August 2019) - Lai, Wing-Fu; Lin, Marie; Wong, Wing-Tak
Abstract : miRNA is a class of short noncoding RNA that regulates gene expression at the post-transcriptional level. Evidence of age-associated changes in miRNA expression has been collected in models ranging from nematodes to humans; however, there has been little discussion of how to turn our knowledge of miRNA biology into antiaging therapy. This opinion article provides a snapshot of our current understanding of the roles of miRNA in modulating the aging process. We discuss major chemical techniques for modifying the miRNA structure as well as developing delivery systems for intervention. Finally, technical needs to be met for bench-to-clinic translation of miRNA-based interventions are highlighted for future research. Highlights: The accumulated knowledge of miRNA biology has established a foundation for using miRNA as a target and a tool for the development of antiaging interventions. The identification of miRNA for antiaging interventions has been facilitated by the use of in silico methods to identify hairpin structures in noncoding and nonrepetitive regions in genome sequences. Diverse miRNA analogs [including phosphorothioate oligodeoxynucleotides (ODNs), locked nucleic acid (LNA) oligonucleotides, and peptide nucleic acids (PNAs)] have been generated to enhance the gene-silencing efficiency of miRNA therapeutics. Both viral and nonviral systems have been developed to deliver miRNA therapeutics, and some allow real-time tracking of the delivery process and codelivery of multiple agents.